The role of multislice computerized tomography angiography in assessing postoperative vascular complications in liver transplant patients - TÜRK, Yaşar (Turk J Med Sci, 2019)
BACKGROUND/AIM: Vascular complications can be detected in liver transplant patients. Digital subtraction angiography has served as the gold standard to make this diagnosis; however, due to its invasive nature, ultrasonography is used for the preliminary evaluation. The purpose of this study was to evaluate the role of multislice computerized tomography angiography (MSCTA) in the detection of vascular complications of symptomatic and asymptomatic liver transplant patients and to compare the results with Doppler ultrasound (Doppler US) findings. MATERIALS AND METHODS: Fifty-three liver transplant patients (6 symptomatic, 47 asymptomatic) underwent Doppler US examination followed by an MSCTA. The findings in each modality were interpreted in a blinded fashion and then compared. RESULTS: MSCTA detected 15 abnormalities, none of which were detected by Doppler US. There were hepatic and splenic artery aneurysms (n = 4) and various stenoses (n = 4), infrarenal aortic anastomosis (n = 4), vena cava inferior thrombosis (n = 1), arteriovenous malformation (n = 1), and esophageal varices (n = 1). CONCLUSION: MSCTA detected more lesions and we believe that it should be considered as a road map for Doppler US follow-ups as well as a routine screening modality for early detection of vascular complications in symptomatic and asymptomatic liver transplantation patients that may be missed by Doppler US.